Enhancing Palm Sugar SMEs' Competitive Advantage in Kalisidi Via Innovative Packaging and E-Commerce Training - Praatmana, Nanang Dwi; Sari, Kartika Dwi Chandra; Cahyaningdyah, Dwi; Lestari, Endah Prapti; Athoillah (Indonesian Journal of Devotion and Empowerment, 2025)
Palm sugar production in Semarang Regency has excellent potential to the abundance of palm trees that thrive. One of the production centers is Kalisidi Village, which is located on a plateau with hilly topography and green vegetation. The local community has maintained traditional production methods for generations, from manual sap harvesting to natural firewood processing. Although these products have authentic appeal and high quality, manufacturers face the challenge of increasingly fierce competition with other businesses that have adopted modern technology. Strategic solutions can be implemented to help palm sugar MSMEs in Kalisidi Village maintain a sustainable competitive advantage through innovation in packaging design. Packaging design training using applications such as Canva are expected to produce attractive, informative, and functional packaging that can increase product appeal while strengthening the brand image. Digital marketing through e-commerce platforms is an advanced  strategic solution to expand market reach. Assistance in digital business processes can increase understanding of data-based marketing and direct interaction with consumers. With the implementation of this community service program, participants have gained an understanding of how to create innovative packaging designs and develop appropriate digital marketing strategies. The follow-up to this community service activity is the continued guidance and monitoring of participants to ensure the sustained implementation of innovative packaging design and effective digital marketing strategies.